State Corporations and Structural Changes in the Economy - V. E. Dementiev (Управление)
The article focuses attention on a possible contribution of the state corporations to long-term results of economic development. It is shown that such corporations can make the significant contribution to ensuring dynamic efficiency of economy, to implementation of structural shifts in production. The role of the state corporations in formation of the infrastructure necessary for wide use of essentially new technologies is analyzed.